"Do you like cookies?" Adolescents' skeptical processing of retargeted Facebook-ads and the moderating role of privacy concern and a textual debriefing. (April 2017) - Zarouali, Brahim; Ponnet, Koen; Walrave, Michel; Poels, Karolien
Abstract: Adolescents are regularly exposed to commercial messages on social networking sites. There is scant knowledge of how they interact with marketing communications on these social platforms. This study examines how advertising on Facebook is associated with adolescents' ad skepticism, and how this influences their purchase intentions. Also, the moderating role of privacy concern and a textual debriefing about the nature of the advertising technique are investigated. In total, 363 adolescents aged 16–18 years participated in an experimental study. The results show that, in general, retargeted Facebook ads (compared to non-retargeting) lead to higher purchase intentions. However, when textual debriefing is provided or for adolescents with a high privacy concern, skeptical attitude toward retargeting increases, which in turn decreases purchase intentions. These research findings hold some important implications for actors from different fields of expertise, such as policy makers, practitioners and educators. Highlights: Moderated mediation model is tested with retargeted advertising on Facebook. Retargeting leads to higher skepticism, which leads to lower purchase intentions. Debriefing and privacy concern moderate the effect of retargeting on ad skepticism.